AN ANALYSIS OF THE RELATIONSHIP BETWEEN FACE LOSS AND STUDENT AGGRESSION: THE CASE STUDY OF MOHAMMED I UNIVERSITY STUDENTS - Fatmi, Abderrahim (ELTR Journal, 2024)
This research study addresses the influence of face loss on students’ aggressive behaviours among Mohammed I University students in Oujda. The study examines how teachers' and peers’ face-threatening acts affect students’ aggressive behaviours. Using the mixed-methods research design, the research questions explore if face loss affects students' aggressive behaviours, how and to what extent face loss can cause a student to behave aggressively towards teachers and classmates, and the motive behind their aggressive behaviours. Data were collected using a survey that included 243 participants and interviews with 28 students who had experienced classroom face loss. Interview data were coded, and thematically analysed and survey data were quantitatively analysed. Both survey and interview data reveal that face loss does affect students' aggressiveness towards their teachers and peers. Such aggressive behaviours include physical and verbal abuse, direct and indirect aggression, and passive forms of aggression. The results also indicate that classroom face loss leaves students with negative attitudes towards their teachers, peers, and school subjects. Recommendations suggest further research vis-à-vis facework strategies employed by teachers to minimize student face loss and classroom embarrassment.